Hepatic signaling by the mechanistic target of rapamycin complex 2 (mTORC2). Issue 1 (26th September 2013) - Lamming, Dudley W.; Demirkan, Gokhan; Boylan, Joan M.; Mihaylova, Maria M.; Peng, Tao; Ferreira, Jonathan; Neretti, Nicola; Salomon, Arthur; Sabatini, David M.; Gruppuso, Philip A.
Abstract : The mechanistic target of rapamycin (mTOR) exists in two complexes that regulate diverse cellular processes. mTOR complex 1 (mTORC1), the canonical target of rapamycin, has been well studied, whereas the physiological role of mTORC2 remains relatively uncharacterized. In mice in which the mTORC2 component Rictor is deleted in liver [ Rictor ‐knockout (RKO) mice], we used genomic and phosphoproteomic analyses to characterize the role of hepatic mTORC2 in vivo . Overnight food withdrawal followed by refeeding was used to activate mTOR signaling. Rapamycin was administered before refeeding to specify mTORC2‐mediated events. Hepatic mTORC2 regulated a complex gene expression and post‐translational network that affects intermediary metabolism, ribosomal biogenesis, and proteasomal biogenesis. Nearly all changes in genes related to intermediary metabolic regulation were replicated in cultured fetal hepatocytes, indicating a cell‐autonomous effect of mTORC2 signaling. Phosphoproteomic profiling identified mTORC2‐related signaling to 144 proteins, among which were metabolic enzymes and regulators. A reduction of p38 MAPK signaling in the RKO mice represents a link between our phosphoproteomic and gene expression results. We conclude that hepatic mTORC2 exerts a broad spectrum of biological effects under physiological conditions. Our findings provide a context for the development of targeted therapies to modulate mTORC2 signaling.—Lamming, D. W., Demirkan, G., Boylan, J. M., Mihaylova, M. M., Peng, T., Ferreira, J., Neretti, N., Salomon, A., Sabatini, D. M., Gruppuso, P. A. Hepatic signaling by the mechanistic target of rapamycin complex 2 (mTORC2). FASEB J . 28, 300–315 (2014). www.fasebj.org